Effects of Mood and Emotion on a Real-World Working Computer System and Network Environment. - Kruth, John G. (Journal of Parapsychology)
This study used a custom computer system designed to induce anxiety in participants and determine if people who are anxious produce more errors in an independent working computer network. Participants (N = 130) were asked to complete sixteen tasks on a computer in twenty minutes to receive a reward. Each participant self-rated their anxiety levels during the tasks. In addition, 130 sessions were run without a computer operator. The network ran independent of the tasks, and operated continuously during the sessions. The first hypothesis predicted sessions without operators would produce fewer network errors than sessions with operators, but it was not supported (p = 0.35). The second hypothesis predicted that anxious operators would produce more errors on the independent network than those less anxious. Initial analysis indicated an unsupported hypothesis, but the initial design did not properly identify anxious users. A post-hoc revised grouping based on actual reported anxiety resulted in this hypothesis being supported (p = 0.04, d = 0.45) indicating that anxious computer operators may affect network communication. There may be other electronic effects as a result of human emotions. Additional research is necessary to con- firm these results and explore whether the intensity of emotions affects electronics.